Simulation-Based Team Leadership Training Improves Team Leadership During Actual Trauma Resuscitations: A Randomized Controlled Trial. Issue 1 (January 2020) - Fernandez, Rosemarie; Rosenman, Elizabeth D.; Olenick, Jeffrey; Misisco, Anthony; Brolliar, Sarah M.; Chipman, Anne K.; Vrablik, Marie C.; Kalynych, Colleen; Arbabi, Saman; Nichol, Graham; Grand, James; Kozlowski, Steve W. J.; et al.
Abstract : Objectives: Trauma resuscitations are complex critical care events that present patient safety-related risk. Simulation-based leadership training is thought to improve trauma care; however, there is no robust evidence supporting the impact of leadership training on clinical performance. The objective of this study was to assess the clinical impact of simulation-based leadership training on team leadership and patient care during actual trauma resuscitations. Design: Randomized controlled trial. Setting: Harborview Medical Center (level 1 trauma center). Subjects: Seventy-nine second- and third-year residents were randomized and 360 resuscitations were analyzed. Interventions: Subjects were randomized to a 4-hour simulation-based leadership training (intervention) or standard orientation (control) condition. Measurements and Main Results: Participant-led actual trauma resuscitations were video recorded and coded for leadership behaviors and patient care. We used random coefficient modeling to account for the nesting effect of multiple observations within residents and to test for post-training group differences in leadership behaviors while controlling for pre-training behaviors, Injury Severity Score, postgraduate training year, and days since training occurred. Sixty participants completed the study. There was a significant difference in post-training leadership behaviors between the intervention and control conditions (b1 = 4.06, t (55) = 6.11, p < 0.001; intervention M = 11.29, SE = 0.66, 95% CI, 9.99–12.59 vs control M = 7.23, SE = 0.46, 95% CI, 6.33–8.13, d = 0.92). Although patient care was similar between conditions (b = 2.00, t (55) = 0.99, p = 0.325; predicted means intervention M = 62.38, SE = 2.01, 95% CI, 58.43–66.33 vs control M = 60.38, SE = 1.37, 95% CI, 57.69–63.07, d = 0.15), a test of the mediation effect between training and patient care suggests leadership behaviors mediate an effect of training on patient care with a significant indirect effect (b = 3.44, 95% CI, 1.43–5.80). Across all trauma resuscitations leadership was significantly related to patient care (b1 = 0.61, SE = 0.15, t (273) = 3.64, p < 0.001). Conclusions: Leadership training resulted in the transfer of complex skills to the clinical environment and may have an indirect effect on patient care through better team leadership. Abstract : Supplemental Digital Content is available in the text.